Developing local organizational capacity for participatory seed management: Experiences from the Eastern Himalayas - Gurung, Barun; Gurung, Prem (CGIAR System-wide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovations, 2001)
This paper describes the objectives and goals oh participatory seed-management initiative that is presently being conducted in the Sankhuwasabha District of eastern Nepal as part of the Gender, Ethnicity and Agro biodiversity Management" project. The long-term goal of the project is to develop local capacities to effectively manage existing genetic resources through the development of skills that enhance crop improvement. The research is based on an interactive methodology that emphasizes devolution through varying levels of farmer participation in the research process. Both men and women farmers are included in the project, with the requirement that they be involved in farming as a full-time subsistence activity, Specific problems faced by farmers in the area, such as out-migration of men looking for wage-work and a yearly period of food scarcity lasting as long as six months, are highlighted.